Ocho ojos y una ciudad: Burgos a través la cartografía durante la Guerra de la Independencia - Polo, Barbara Martin (Eikonocity. Storia e Iconografia delle Città e dei Siti Europei, 2018)
The Independence War that took place in Spain during 1808 and 1813, originated a complex development of branches of knowledge related to the war, among which it was the science of cartography. Through the production of maps from different points of interest for the troops, we can understand the evolution of techniques used by different armies as well as their mentalities about the cities. This last point must be comprehended from the point of view that any map made over the territory is a subjective projected image, that only reflects this one of interest for its creator. In the case of Burgos, one of the key point of Spain for Napoleón Bonaparte, we have different mental projections of the city during the conflict, something very exceptional. Four versions that make us see the city as they thought it was, according to their particular interests.